Employee Participation in Decision Making, Psychological Ownership, and Knowledge Sharing: Mediating Role of Organizational Commitment in The Gambia Civil Aviation Authority (GCAA) - Muhammed Bah; Meika Kurnia Puji Rahayu (Journal of Religion, Local Politics, and Law, 2025)
This study investigates how employee participation in decision-making and psychological ownership influence knowledge sharing, with organizational commitment as a mediating factor in the Gambia Civil Aviation Authority. Addressing knowledge management challenges and limited empirical research in The Gambia, it explores how engagement and ownership enhance knowledge sharing through stronger commitment. Using a quantitative approach, structured questionnaires were distributed to staff, and data were analyzed through structural equation modeling to test direct and mediated relationships. The results show that both participation in decision-making and psychological ownership significantly and positively affect organizational commitment and knowledge sharing. Furthermore, organizational commitment enhances knowledge sharing and mediates the effects of participation and ownership. These findings highlight the importance of involving employees in organizational decisions and fostering a sense of ownership to overcome barriers to knowledge sharing. Practically, the study suggests that the Gambia Civil Aviation Authority and similar organizations should adopt participatory management and psychological empowerment strategies to build commitment and promote continuous knowledge sharing. Such efforts are vital for operational efficiency, innovation, and sustainable growth. Overall, this research fills a gap in knowledge-sharing studies within African aviation contexts and provides a framework for improving information exchange in resource-limited settings.